2012
DOI: 10.1210/jc.2011-3109
|View full text |Cite
|
Sign up to set email alerts
|

Clinical and Genetic Characteristics of Autoimmune Polyglandular Syndrome Type 3 Variant in the Japanese Population

Abstract: In conclusion, we found notable differences in the clinical and genetic characteristics of APS3v patients and T1D/AITD(-) patients in the Japanese population, and the differences in the clinical characteristics between the two groups may reflect distinct genetic backgrounds including the HLA DRB1-DQB1 haplotypes and CTLA4 gene polymorphisms.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
34
0
6

Year Published

2013
2013
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 41 publications
(42 citation statements)
references
References 36 publications
2
34
0
6
Order By: Relevance
“…Both anti-GAD ab and anti-IA2 ab were negative in cases 24, 25 and 26 in Table 2; however, they were insulin-dependent and showed the positivity for anti-TPO ab and anti-TG ab, and they were included in patients with APS3a. Our previous reports [4,[7][8][9] and present study revealed a remarkable female predominance in APS3a, which agreed with previous reports [10,11]. Among patients with autoimmune diabetes, SPIDDM was the most common type of diabetes, and the positive rate of anti-GAD ab was higher than that of anti-IA2 ab.…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…Both anti-GAD ab and anti-IA2 ab were negative in cases 24, 25 and 26 in Table 2; however, they were insulin-dependent and showed the positivity for anti-TPO ab and anti-TG ab, and they were included in patients with APS3a. Our previous reports [4,[7][8][9] and present study revealed a remarkable female predominance in APS3a, which agreed with previous reports [10,11]. Among patients with autoimmune diabetes, SPIDDM was the most common type of diabetes, and the positive rate of anti-GAD ab was higher than that of anti-IA2 ab.…”
Section: Discussionsupporting
confidence: 93%
“…Only one article reported clinical and genetic characteristics of adult APS3, and we found one more article which reported the incidence of APS3 in children with type 1 diabetes [10,11].…”
Section: Introductionmentioning
confidence: 99%
“…With a relative prevalence of approximately 40%, PAS type III is the most frequent subtype and encompasses type 1 diabetes (T1D) and an autoimmune thyroid disease, AITD [1]. T1D may occur with an autoimmune-induced hypothyroidism (generally caused by chronic lymphocytic Hashimoto's thyroiditis, HT) or hyperthyroidism (caused by Graves' disease, GD) differing in genetic, serologic, and clinical presentation [17]. Additional (non-) glandular autoimmune diseases are common in PAS III.…”
Section: Introductionmentioning
confidence: 99%
“…Horie et al (4) reported the chronological order of T1D and GD development in 30 Japanese patients with APS3v. Ten percent developed T1D and GD simultaneously, 60% developed GD before the onset of T1D and 30% developed GD after the onset of T1D.…”
Section: Discussionmentioning
confidence: 99%
“…With regard to the clinical characteristics of APS3v (including both patients with T1D plus GD and those with T1D plus Hashimoto's thyroiditis), marked female predominance, a slowly progressive clinical course with older T1D onset age, a higher prevalence of GAD antibodies and a higher level of GAD antibodies were observed in APS3v patients compared to T1D patients without AITD (4,8). The prevalence of IA-2 antibodies was significantly higher in acute-onset T1D than in slowly progressive T1D among APS3v patients (4).…”
Section: Discussionmentioning
confidence: 99%